"Internet of Things" Real-Time Free Flap Monitoring. Issue 1 (January 2018) - Kim, Sang Hun; Shin, Ho Seong; Lee, Sang Hwan
Abstract : Background: Free flaps are a common treatment option for head and neck reconstruction in plastic reconstructive surgery, and monitoring of the free flap is the most important factor for flap survival. In this study, the authors performed real-time free flap monitoring based on an implanted Doppler system and "internet of things" (IoT)/wireless Wi-Fi, which is a convenient, accurate, and efficient approach for surgeons to monitor a free flap. Methods: Implanted Doppler signals were checked continuously until the patient was discharged by the surgeon and residents using their own cellular phone or personal computer. If the surgeon decided that a revision procedure or exploration was required, the authors checked the consumed time (positive signal-to-operating room time) from the first notification when the flap's status was questioned to the determination for revision surgery according to a chart review. To compare the efficacy of real-time monitoring, the authors paired the same number of free flaps performed by the same surgeon and monitored the flaps using conventional methods such as a physical examination. Results: The total survival rate was greater in the real-time monitoring group (94.7% versus 89.5%). The average time for the real-time monitoring group was shorter than that for the conventional group (65 minutes versus 86 minutes). Conclusions: Based on this study, real-time free flap monitoring using IoT technology is a method that surgeon and reconstruction team can monitor simultaneously at any time in any situation. Abstract : Supplemental Digital Content is available in the text